Steinernema diaprepesi nguyen & duncan (Rhabditida: Steinernematidae), a new entomopathogenic nematode from Brazil - Horta, André B. [UNESP]; Damascena, Alixelhe P. [UNESP]; DE CARVALHO, Vanessa R. [UNESP]; Ribeiro, Murilo F. [UNESP]; Castro, Bárbara M.C.; Wilcken, Carlos F. [UNESP]; Zanuncio, José C.; Wilcken, Silvia R.S. [UNESP] (My University, 2021)
Entomopathogenic nematodes (EPNs) can control pests due to their mutual association with bacteria. The use of these biological control agents is increasing worldwide due to advances in research about its control efficiency, range of action and mass production. The identification of EPNs adapted to specific environmental and climatic conditions is important for sustainable pest suppression in integrated management (IPM) programs. The objective is to report, for the first time, the occurrence of the Steinernema diaprepesi in Brazil. Steel mesh traps with Galleria mellonella Linnaeus (Lepidoptera: Pyralidae) larvae were buried in red latosol cultivated with Eucalyptus. Infective juveniles (IJs) were isolated from dead larvae and multiplied in healthy ones of this host to confirm its pathogenicity and to start a laboratory population from the strain found in the field. The DNA of the IJs was extracted and amplified using PCR technique with the universal primers D2A and D3B. The detection of S. diaprepesi is the first report of this nematode in Brazil, increasing the knowledge about its distribution in the world and the diversity of EPNs that must be considered as agents of biological pest control in the country.
Keywords: Biological control; Crop protection; Galleria mellonella; Infective juveniles; PCR